2016
DOI: 10.22237/jmasm/1462076460
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Persian Blog Attitude Questionnaire: An Evidence-Based Approach

Abstract: Validity evidence is provided for a Persian blog attitude questionnaire (P-BAQ). P-BAQ was administered to 565 Iranians and factor analysis and rating scale model identified affective, behavioral, and perseverance, and confidence dimensions underlying the data. P-BAQ's validity argument was supported by the theoretical and psychometric evidence, although adding a few items to the instrument would improve its construct representativeness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
1
1
0
Order By: Relevance
“…Therefore, it was decided to remove it to meet the criterion of unidimensionality or primary dimension of the variable, to fit the data in the model, and to provide validity to the instrument [26]. Once it was removed from the analysis, the fit statistics of the remaining items ranged from 0.5 to 1.5, which is consistent with related studies in other fields [25,27] and provides support for construct validity. At the person level, 35.5% of the small-scale farmers did not fit the model, which contrasts with the lower value of 15.7% obtained by Arias González et al [23].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Therefore, it was decided to remove it to meet the criterion of unidimensionality or primary dimension of the variable, to fit the data in the model, and to provide validity to the instrument [26]. Once it was removed from the analysis, the fit statistics of the remaining items ranged from 0.5 to 1.5, which is consistent with related studies in other fields [25,27] and provides support for construct validity. At the person level, 35.5% of the small-scale farmers did not fit the model, which contrasts with the lower value of 15.7% obtained by Arias González et al [23].…”
Section: Discussionsupporting
confidence: 57%
“…This model has been used to calibrate scales, instruments, and tests to verify their validity and reliability for the construction of measurements in various areas such as education, the health sciences, and the social sciences [25][26][27][28][29]. However, no studies were found in which this model was applied to verify the validity and reliability of scales, tests, or instruments aimed at measuring the entrepreneurial skills of small-scale farmers [12].…”
Section: Introductionmentioning
confidence: 99%